Um herói contra a corrupção? Perspectiva de análise de Tropa de Elite II e o processo de estetização da violência no cinema brasileiro contemporâneo - Carias, Felipe Biguinatti (2019)
Elite Squad: The Enemy Within (2010) by José Padilha was a brazilian cinematographic work which were produced an extense dialogue about the problem of brazilian public security specially in the case of drug war: formation of organized crime and militias. Faced with many semantic debates the purpose of this respective research support three hypotheses about the cinematographic work and its sucesssive discussion. The first hypothesis aims reflect about the extensive interpretation about national contemporary cinema and your categorization as a national blockbuster. According some authors readings, for exemple, Marcelo Ikeda, Lúcia Nagib, Anita Simis etc. The national cinema would be producing an aesthetic narrative of nationalization or aesthetization of brazilian social issues, following patterns of Renato Ortiz’ interpretation, breaking cultural and territorial barriers and getting major capital circularities and announcements. However the dialogue of such an interpretation, the authors don’t come up with any possibilities of polissemia between spectator and done work. The rhetoric of Cultural Industrial and univocal interpretation is constantly naturalized. This research breaks this interpretation when discussing as critics in the newspapers Folha de São Paulo and O Globo what shows that even being an Industrial Culture’s work it’s also polysemy. The second hypothesis begins with the following question: why Elite Squad II provided strong social argument? Thereby the hypothesis is supported by three social issues: aestheticization of violence and the ordinary world; rhetoric of the hypernaturalist narrative of those who "really lived given the situation"; reality shows and the film genre Found Footage. This three subjects helps problematize the third and the last one hypothesis. Elite Squad II was interpreted as a work that "describes" the mismanagement of the Brazilian public space by the fact of naturalize and dialogue with the extremely consolidated interpretation in brazilian historical memory: the concept of patrimonialism systematized by Raymundo Faoro and the UDN party.